1987
DOI: 10.1177/019251387008002004
|View full text |Cite
|
Sign up to set email alerts
|

Time Used for Household Work

Abstract: The purpose of this study was to compare the time-use of school-age children in single-parent/one-earner, two-parent/one-earner, and two-parent/two-earner families to determine whether or not there were differences in actual and relative amounts of time used for household work. The sample consisted of 170 households with school-age children. Two instruments were used: a time use chart and a nine-page survey questionnaire. Findings were that employment of the homemaker did not appear to contribute to difference… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1990
1990
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…Geerken and Gove (1983), Peters and Haldeman (1987), and Sanik (1981) found no difference in total time spent on household tasks among children in dual-earner and traditional families. However, in a study of sixth-grade children, Medrich and associates (1982) reported that children of employed mothers performed more chores and spent more time on chores than children whose mothers were not in the work force.…”
Section: Mother's Employmentmentioning
confidence: 98%
“…Geerken and Gove (1983), Peters and Haldeman (1987), and Sanik (1981) found no difference in total time spent on household tasks among children in dual-earner and traditional families. However, in a study of sixth-grade children, Medrich and associates (1982) reported that children of employed mothers performed more chores and spent more time on chores than children whose mothers were not in the work force.…”
Section: Mother's Employmentmentioning
confidence: 98%
“…From the late 1970s until the early 1990s, research on children's involvement in unpaid household labour was conducted by asking parents about their children's contribution (Blair 1992;Cogle and Tasker 1982;Gill 1998;Goodnow 1989;Peters and Haldeman 1987;Shamgar-Handelman 1986;Thrall 1978;White and Brinkerhoff 1981;White and Brinkerhoff 1987). Within the new sociology of childhood it is now considered one-sided only to ask adults to speak on behalf of their children (James and Prout 1990).…”
Section: Previous Research On Children's Participation In Household Workmentioning
confidence: 99%
“…Some authors have found that children's participation in household labour increases according to the nature of parents' employment, such as in dual-earner households (Blair 1992;Thrall 1978), or single-headed households (Peters and Haldeman 1987;White and Brinkerhoff 1981). Unsurprisingly, most studies of children's household work have focused on gender as the main determinant of labour allocation (Burns and Homel 1989;Deere and León 1982;Johnson et al 1995;McHale et al 1990;Thrall 1978;White and Brinkerhoff 1981).…”
Section: Previous Research On Children's Participation In Household Workmentioning
confidence: 99%
“…For example, families with single parents or working mothers may lack the time resources of other families, necessitating more housework by adolescents. Numerous researchers, including Peters and Haldeman (1987), Goldscheider and Waite (1991), Hilton and Haldeman (1991), Demo and Acock (1993), Gager et al (1999), andCapizzano et al (2004), have found that teenagers, especially girls, living in single-parent households spend more time in housework (including child care) than those in dual-parent households. Call et al (1995) reported greater housework among teens with working mothers.…”
Section: Literature Reviewmentioning
confidence: 99%